THE IMPLEMENTATION OF VIRTUAL EXHIBITION PROJECT IN ENGLISH FOR TOURISM CLASS FOR UNIVERSITY STUDENTS - Suprayogi Suprayogi; Pranoto Budi Eko (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2020)
Currently, studies on English for Tourism course mainly focuses on need analysis and material development. A few studies highlight the teaching methods for successful learning of the course. This study discusses the implementation of virtual exhibition simulation as a project based learning in the course of English for Tourism enrolled by students of tertiary education majoring English Literature. It aims at revealing the learning process as well as revealing the opportunities and challenges of the activity. Five lecturers are selected as the subject of the study. The data collected through semi structured interview and further qualitatively analysed by seeing the common and unique features. The findings suggest that the implementation of virtual exhibition project should be followed by lecturers teaching strategies in the step of preparation, rehearsal and exhibition in order to achieve learning objectives. Despite the technical challenge on internet connection and students reluctance that lecturers should cope with, this activity is seen as an alternative method that reflect contextual learning and give students English learning opportunity through intensive interaction and creativity.